Gastric secretion of platelet activating factor and precursors in healthy humans: effect of pentagastrin. Issue 8 (August 1993) - Sobhani, I; Denizot, Y; Hochlaf, S; Rigaud, D; Vatier, J; Benveniste, J; Lewin, M J; Mignon, M
Abstract : The release of platelet activating factor (PAF-ACETHER or PAF) and its precursors in the gastric lumen was assessed in 13 normal subjects in basal condition and after stimulation by gastrin. Acid, pepsin, and sialic acid outputs were determined under the same conditions. Gastric juice was collected using a nasogastric tube after overnight fast in basal condition for 60 minutes, then under pentagastrin infusion (6 micrograms/kg/hr for 60 minutes). Platelet activating factor was detected at low concentration in 4/13 subjects under basal condition (mean (SEM) 1.2 (0.6) pg/hr) while high concentrations of lyso platelet activating factor (6.1 (1.8) microgram/hr) and of alkyl-acyl-glycerophosphocholine (AAGPC) (11.5 (3) micrograms/hr) were found in 13 and 11 subjects, respectively. Platelet activating factor was not detected during pentagastrin infusion, while lyso platelet activating factor and alkyl-acyl-glycerophosphocholine were detected in 13 and in 12 subjects, respectively. Compared with the basal condition these platelet activating factor precursors increased significantly (p < 0.001) going up to fivefold baseline (31.8 (6.8) micrograms/hr and 53 (9.3) micrograms/hr respectively) in response to pentagastrin. There was a positive correlation between platelet activating factor precursors and acid or pepsin output but not between platelet activating factor precursors and sialic acid. As sialic acid may be considered an index of mucus glycoprotein degradation, it seems that gastrin stimulation of gastric epithelial cells results in a concomittant secretion of platelet activating factor precursors, acid, and pepsin irrespective of mucus glycoprotein degradation.